Heparin promotes rapid fibrillation of the basic parathyroid hormone at physiological pH. Issue 22 (9th August 2022) - Lauth, Luca M.; Voigt, Bruno; Bhatia, Twinkle; Machner, Lisa; Balbach, Jochen; Ott, Maria
Abstract : In acidic secretory granules of mammalian cells, peptide hormones including the parathyroid hormone are presumably stored in the form of functional amyloid fibrils. Mature PTH, however, is considerably positively charged in acidic environments, a condition known to impede unassisted self‐aggregation into fibrils. Here, we studied the role of the polyanion heparin on promoting fibril formation of PTH. Employing ITC, CD spectroscopy, NMR, SAXS, and fluorescence‐based assays, we could demonstrate that heparin binds PTH with submicromolar affinity and facilitates its conversion into fibrillar seeds, enabling rapid formation of amyloid fibrils under acidic conditions. In the absence of heparin, PTH remained in a soluble monomeric state. We suspect that heparin‐like surfaces are required in vivo to convert PTH efficiently into fibrillar deposits. Abstract : At low physiological pH, the parathyroid hormone is a positively charged peptide that remains in a soluble monomeric state over time. We show in vitro that high affinity binding to the polyanion heparin leads to higher‐order assemblies and, finally, PTH fibrillation. We propose that PTH conversion into functional amyloid fibrils might rely on similar polyanionic structures in vivo .